Development of solid dispersion system from milk thistle dry extract by solvent method - B. A. Perez; I. E. Kauhova; I. I. Terninko; O. N. Abrosimova; E. V. Vishnyakov; N. S. Pivovarova (Разработка и регистрация лекарственных средств, 2025)
Introduction. Silymarin is one of the main components used in preparations for hepatotropic therapy. Silymarin is contained in the dry extract of seeds and fruits of milk thistle (Silybum marianum L. Gaertn.), however it has poor bioavailability due to the crystalline state and low solubility of silymarin flavolignans in water at room temperature, as well as their poor absorption. One of the methods for increasing the bioavailability of medicinal substances consists in their introducing into solid dispersion systems (SDS). The most suitable method for obtaining SDS with extracts is the solvent method, since it does not require the use of a high temperature regime during the obtaining process of SDS.Aim. To develop the technology for solid dispersion system from milk thistle dry extract by solvent method to increase the bioavailability of this phytosubstance.Material and methods. The obtaining of the solid dispersion systems from milk thistle dry extract by solvent method was carried out with polyvinylpyrrolidone (PVP K-29/32), polyvinylpyrrolidone vinyl acetate 6 : 4 (PVPVA 64), hydroxypropylmethylcellulose (HPMC), gelatin and sodium lauryl sulfate (SLS). The quality indicators of the SDS: particle size distribution, bulk density, residual humidity and hygroscopicity were carried out according to the methods of the State Pharmacopoeia of the Russian Federation (GP RF) XV edition. The quantitative determination of biologically active substances (BAS) was carried out in accordance with the GP RF XV ed. by the amount of flavolignans in terms of silybin.Results and discussion. During the development of solid dispersion systems by solvent method, SDS samples from milk thistle dry extract (MTDE) with different polymers were studied. As a result of studying the particle size distribution, several SDS samples were selected. The SDS samples were compared with the MTDE sample. The "Dissolution" test showed that the micronization of MTDE in form of SDS by solvent method, containing polyvinylpyrrolidone vinyl acetate – PVP VA 64 is the best alternative for increasing the silybin releasing-degree from the extract and increasing its bioavailability. According to the content of the sum of flavolignans in terms of silybin, the selected SDS sample meets the requirements of the normative documentation for milk thistle dry extract. In addition, the conditions for the development of SDS do not significantly affect the quantitative content of silybin compared with the content of the control sample of MTDE. The technological characteristics of SDS have been investigated and their qualitative improvement compared to the MTDE sample has been established. The interaction between the polymer carrier and the milk thistle extract was evaluated by the IR-fourier spectroscopy method.Conclusion. The SDS from milk thistle dry extract was developed by solvent method. For the developed SDS, quality indicators such as the content of the sum of flavolignans in terms of silybin, residual humidity, bulk density, particle size distribution and hygroscopicity were determined. The solid dispersion system from milk thistle extract was analyzed by IR-fourier spectroscopy. The physico-chemical compatibility between the milk thistle extract and the polymer-carrier polyvinylpyrrolidone vinyl acetate is shown. The development of the SDS from milk thistle dry extract significantly increased the bioavailability of the phytosubstance by increasing the silybin releasing-degree of the SDS by 3 times compared with the control sample of MTDE.